Pengaruh kualitas produk, harga, dan social media marketing tiktok terhadap keputusan pembelian produk Corkcicle di Indonesia - Fricilla Badzlin; Permana, Erwin; Ateniyanti (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This research aims to marketing on purchasingl decisions for Corkcicle products in Indonesia. Thisl research isl quantitativelresearch. Thel population usedl in thisl research werel consumers whol played social media TikTok andhad purchased Corkcicle products, with al sample size ofl 112 respondentsl using thel Rao Purba lformula.Thel data collection methodl is through questionnaires. This research uses thel SmartPLS l3.0l analysistechnique. Thel results ofl this research show thatl product qualityl has al positive andl significant effectlon purchasingl decisions withl a lT-Statistic valuel of l2.494 (> 1.96) andl P- Values l0.013 (< 0.05), pricelhas al positive andl significant effectl on purchasingl decisions withl a lT-Statistic valuel of 1.989 (>1.96)andl P-Values l0.047 (<0.05), Social media marketingl is positivel and significantl on purchasingldecisions withl a lT-Statisticl value ofl 3.042 (>1.96) and lP-Values l0.002 (<0.05), Thel variables productquality, pricel and sociall media marketingl simultaneously havel a significantl influence onl purchasing decisionslwith calculated F of 108 > F table of 2,69.